Controlled fabrication and performances of single-core/dual-shell hierarchical structure m-TNO@TiC@NC anode composite for lithium-ion batteries. (1st May 2020) - Luo, Jing; Peng, Jiao; Zeng, Peng; Xiao, Wensheng; Li, Wangwu; Wu, Zhenyu; Wang, Ying; Miao, Changqing; Chen, Gairong; Shu, Hongbo; Wang, Xianyou
Abstract: Oriented construction of high-performance mesoporous TiNb2 O7 (m-TNO) is important to the design innovation of anode material for next-generation lithium-ion batteries (LIBs) due to the high capacity and long cyclic life of m-TNO. However, the conductivity enhancement of m-TNO and thus accelerating Li + transfer is still the key point to realize its practical application in LIBs. In this work, a synergistic strategy based on the single-core/dual-shell m-TNO@TiC@NC hierarchical structure is put forward, which is achieved by using m-TNO as host architecture as well as TiC and N-doped carbon layer (NC) as dual-shell layers. The results show that the m-TNO@TiC@NC hierarchical structure can not only provide an integrated conductive network to improve the conductivity of m-TNO, but also can establish a reinforced structure to maintain the anode stability. Besides, it is found that the m-TNO@TiC@NC composite has a high capacity of 328.6 mAh g −1 at 0.5 C after 200 cycles and a high-rate capacity of 186.4 mAh g −1 at 5 C by galvanostatic discharge-charge tests. Therefore, this kind of special single-core/dual-shell structure design can convincingly enhance the conductivity of m-TNO and facilitate the Li + transfer rate, thus promoting electrochemical performances of LIBs due to the synergistic effect of dual-shell layers. Graphical abstract: Image 1 Highlights: The m-TNO@TiC@NC composite is achieved by using m-TNO as host architecture as well as TiC and NC as dual-shell layers. The m-TNO@TiC@NC composite shows the single-core/dual-shell hierarchical structure. The new-type ceramic material TiC is used as conducting layer. The m-TNO@TiC@NC composite displays good electrochemical performance.